Analisis Penentuan Penginapan dengan Metode AHP dan Promethee - Muntiari, Novita Ranti; Sunardi, Sunardi; Fadlil, Abdul (Universitas Diponegoro, 2020)
Traveling to a place with a period of days requires a place to stay. The problem is determining accommodation according to the wishes of different visitors, such as prices according to the type of lodging, complete facilities or not at the inn, and the distance to other places from the inn. There are too many lodging options that make it difficult for visitors to determine the best alternative. This research focuses on lodging in the Malioboro area of Yogyakarta by using the criteria of distance, price, class of accommodation, room facilities, and supporting facilities. AHP method is used to determine the weight of each criterion, then the weight of each criterion is calculated using Promethee with the usual or general criteria preference type, to produce a net flow value. Combination of two methods is better because the AHP method is more suitable to be used to find the weight of each criterion and Promethee by using a preference index as needed by producing suitable alternatives. The result of AHP and Promethee calculations obtained with the PP3 alternativewith a net flow value of 0.2 to be the first rank and it can be stated that the existing criteria are very suitable for what visitors want.